2020
DOI: 10.1109/jsen.2019.2946095
|View full text |Cite
|
Sign up to set email alerts
|

Bi-LSTM Network for Multimodal Continuous Human Activity Recognition and Fall Detection

Abstract: This paper presents a framework based on multi-layer bi-LSTM network (bidirectional Long Short-Term Memory) for multimodal sensor fusion to sense and classify daily activities' patterns and high-risk events such as falls. The data collected in this work are continuous activity streams from FMCW radar and three wearable inertial sensors on the wrist, waist, and ankle. Each activity has a variable duration in the data stream so that the transitions between activities can happen at random times within the stream,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 198 publications
(78 citation statements)
references
References 35 publications
0
77
0
1
Order By: Relevance
“…For sequential gaits, the network is able to learn the dependencies related to the order of the gaits, where the transition between two different gait styles is the key to reinforce the inter-connections among the cells on two Bi-LSTM layers. A dual layer architecture has higher capabilities than a single layer one; however, there is a trade off between the number of layers and the computational complexity to achieve a boost in accuracy with feasible network training time, as shown in previous work [27], [28].…”
Section: B Bi-lstm Recurrent Neural Network Structurementioning
confidence: 97%
See 3 more Smart Citations
“…For sequential gaits, the network is able to learn the dependencies related to the order of the gaits, where the transition between two different gait styles is the key to reinforce the inter-connections among the cells on two Bi-LSTM layers. A dual layer architecture has higher capabilities than a single layer one; however, there is a trade off between the number of layers and the computational complexity to achieve a boost in accuracy with feasible network training time, as shown in previous work [27], [28].…”
Section: B Bi-lstm Recurrent Neural Network Structurementioning
confidence: 97%
“…Typical hard fusion methods include majority voting (MV), weighted majority voting (WMV), Recall Combiner (RC) and Naive Bayes Combiner (NBC) [39]. In our previous work [27], it was shown that NBC outperformed other hard fusion methods, and this was chosen to be the hard fusion approach also in this paper. Compared to soft fusion, NBC attempts to gather the results from all the N classifiers to build a classifier ensemble.…”
Section: A Feature Fusion With Conventional Classifiersmentioning
confidence: 98%
See 2 more Smart Citations
“…It can utilize the sequentiality to learn and extract sequential features from a sequential input data stream. In [25], H. Li et al presented a framework based on multilayer bi-LSTM network (bidirectional Long Short-Term Memory) for multimodal sensor fusion to sense and classify daily activities' patterns and high-risk events such as falls. In [26], J. Zhu et al proposed a deep learning model composed of 1-D convolutional neural networks (1D-CNNs) and long shortterm memory (LSTM).…”
Section: Introductionmentioning
confidence: 99%